2017
DOI: 10.1111/ijcp.13033
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms at presentation to the emergency department: Predicting outcomes and changing clinical practice?

Abstract: Background: The type and number of symptoms in emergency patients differ widely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 23 publications
(33 reference statements)
0
20
0
Order By: Relevance
“…Additionally, these studies focused on single, main, presenting, or chief complaints. Therefore, it was never taken into account that most patients present with more than one symptom [3,7]. The model of chief complaint or main symptom heavily relies on several steps of selection and reduction of information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, these studies focused on single, main, presenting, or chief complaints. Therefore, it was never taken into account that most patients present with more than one symptom [3,7]. The model of chief complaint or main symptom heavily relies on several steps of selection and reduction of information.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies were limited to the investigation of single symptoms. These did not take into account that patients reporting more than one symptom at presentation are the norm rather than the exception [3,7], and that combinations of certain symptoms might be able to predict adverse outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously described that headache is among the most prevalent symptoms in ED patients, affecting more than one out of six patients, if patient-reported symptoms are not screened, or filtered by physicians [12]. As the majority of ED patients report more than one symptom [13], and headache patients report a median of four symptoms (often in combination with nonspecific complaints [14,15]), it is highly likely that previous studies have underreported headache, potentially due to inclusion bias and the physician filter. Constructs such as "chief complaint" or "main symptom" heavily rely on several steps of selection and reduction of information [16]-physicians tending to focus on frequent and specific presenting symptoms [17].…”
Section: Introductionmentioning
confidence: 99%
“…However, over-reporting is conceivable, as more than one symptom could be chosen. In fact, the majority of our patients reported more than one symptom [38], the number of symptoms being unrelated to medically important outcomes. To our knowledge, no studies have reported age-stratified prevalence of underlying diseases in the last two decades.…”
Section: Discussionmentioning
confidence: 81%
“…First, this was a single-center study, and external validity is therefore limited. However, our ED cohort seems to represent the population of other urban, European EDs, with over two-thirds of patients having their origin in central or northern Europe [5] and the proportion of foreigners in our ED being about 32% [38]. An inclusion bias is possible, because almost 17% of patients could not be screened, and 6% were lost to follow-up.…”
Section: Discussionmentioning
confidence: 99%